Seeking Adventure: Relationship between Emotional Intelligence and Sensation Seeking among University Students - Sohail, Rahma; Nusrat, Aminah; Umar, Ayesha (Annals of Human and Social Sciences, 2024)
The study at present aims to find a relationship between sensation seeking and emotional intelligence among the university students in Islamabad and Rawalpindi. In the present age, there is an increase in the degree of sensation seeking in university students. Emotional intelligence has been since the humanity arose in the history. The university students from cities of Rawalpindi and Islamabad constituted the universe of the present research. The Schutte Self Report Emotional Intelligence Test (SSEIT) and brief version of Sensation Seeking scale by Zuckerman were used to gather data. The results obtained via statistical analysis found a positive correlation between sensation seeking and no significant differences in sensation seeking in males and females. No significant variation in emotional intelligence of males and females were found. The results also found that emotional intelligence explained 17 % variance in sensation seeking. Our results suggest that it would be worthwhile to expand the treatment of sensation seeking to investigate a broader range of outcomes and within the scope of developmental tasks that accompany the transition to adulthood. Doing so might eventually lead to a better understanding of how sensation seeking might be channeled towards healthy rather than health-compromising outcomes.